Bioactive Alpha-Pyrone and Phenolic Glucosides from the Marine-Derived Metarhizium sp. P2100 - Zhong-Lian Ma; Zhi-Pu Yu; Yao-Yao Zheng; Na Han; Ya-Hui Zhang; Shu-Yue Song; Jun-Qiu Mao; Jiao-Jiao Li; Guang-Shan Yao; Chang-Yun Wang (Journal of Fungi, 2022)
Glycoside compounds have attracted great interest due to their remarkable and multifarious bioactivities. In this study, four hitherto unknown 4-methoxy-β-D-glucosyl derivatives were obtained and identified from the marine-derived fungus Metarhizium sp. P2100, including three alpha-pyrone glycosides (1–3) and one phenolic glycoside (4). Their planar structures were elucidated by comprehensive spectroscopic analysis, including 1D/2D NMR and HRESIMS. The absolute configurations of 1–3 were determined by a single-crystal X-ray crystallographic experiment, a comparison of the experimental, and a calculated electronic circular dichroism (ECD) spectra, respectively. Compounds 2 and 3 are a pair of rare epimeric pyranoside glycosides at C-7 with a core of aglycone as 2H-pyrone. Compounds 1–4 exhibited weak anti-inflammatory activities. In particular, compounds 1–3 displayed inhibitory activities against α-amylase, showing a potential for the development of a new α-amylase inhibitor for controlling diabetes.